РАДІОХЕМОЕКОЛОГІЧНИЙ СТАН БУХТИ КОЗАЧА (ЧОРНЕ МОРЕ) У ВІДНОШЕННІ ТОКСИЧНИХ МЕТАЛІВ HG, SR, PU ТА PO - Терещенко, Н. М.; Лазоренко, Г. Є.; Мірзоєва, Н. Ю.; Єгоров, В. М.; Плотіцина, О. В. (Marine Ecological Journal, 2023)
Evaluation of radio-chemoecological state of the Kazachja Bay in respect of certain pollutants was carried out. The levels of radioactive and chemical contamination of the ecosystem components of the Kasachja Bay by metals: chemical toxicant mercury and the radioactive isotopes: anthropogenic (90Sr and 238,239,240 Pu) and natural (210Po) were identified and analyzed. The dose commitments generated by natural and artificial radionuclides to indicator species of hydrobionts were calculated. The Polikarpov’s Conceptual radiochemoecological model of zonality was used to estimate of the ecological effects of radioactive pollutants in biotic components of the ecosystem of this bay. Radio-chemoecological state of the Kasachja Bay did not raise concerns about mercury, the most toxic heavy metals in the marine environment and man-made radionuclides strontium and plutonium. The dominant contribution to the radiation doses to the Black Sea hydrobionts in the Kazachja Bay was made by natural radionuclide 210Po, and the part of the contribution of man-made radionuclides (90Sr and 239,240 Pu) was not more than 0.3 %. The critical links in the ecosystem of the bay with the highest levels of accumulation for each metal have been defined.